Diabetes-Tuberculosis Care in Eswatini: A Qualitative Study of Opportunities and Recommendations for Effective Services Integration - Victor Williams; Victor Williams; Victor Williams; Alinda G. Vos-Seda; Alinda G. Vos-Seda; Samson Haumba; Lindiwe Mdluli-Dlamini; Marianne Calnan; Diederick E. Grobbee; Kennedy Otwombe; Kennedy Otwombe; Kerstin Klipstein-Grobusch; et al. (Frontiers Media S.A., 2023)
Objective: This study describes the availability of basic services, equipment, and commodities for integrated DM-TB services, best practices by healthcare workers, and opportunities for better integration of DM-TB care in Eswatini.Methods: A qualitative design was used. Twenty-three healthcare workers participated in a survey and key informant interview.Results: Most respondents indicated DM and TB care are integrated and clients access blood pressure and fasting/random blood glucose assessment. Few respondents indicated they provide visual assessment, hearing assessment, and HbA1c testing. Respondents experienced stockouts of urinalysis strips, antihypertensive drugs, insulin, glucometer strips, and DM drugs in the previous 6 months before the interview. Four main themes emerged from the qualitative interviews-quality and current standards of care, best practices, opportunities, and recommendations to improve integrated services delivery.Conclusion: While DM care is provided for TB patients, the implementation of integrated DM-TB services is suboptimal as the quality and current standards of care vary across health facilities due to different patient-level and health system challenges. Some identified opportunities must be utilized for a successful DM-TB integration.